P65 High rates of referral and voluntary clinic attendance among community members screened with high cardiovascular disease risk using citizen Science and engagement in Ethiopia. (26th August 2022) - Kedir, Kiya; Mesfin, Firaol; Getachew, Hailemichael; Hailu, Belachew; Geremew, Bezinash; Okop, Kufre; Levitt, Naomi; Howe, Rawleigh
Abstract : Background: Cardiovascular disease (CVD) and its risk factors are rising in sub-Saharan Africa, and community level screening has been advocated. The present study was a pilot study utilizing lessons learned from previous citizen science (CS)-facilitated research to understand CVD risk perceptions in Ethiopian communities. The study goal was to assess the feasibility of community CVD screening and referral intervention, assess rates of voluntary clinic attendance, and explore reasons for non-attendance. Methods: A total of 1300 community members were screened from 10 health clinic catchment areas representing urban (Addis Ababa, Adama) and multiple rural sites of increasing distance from Adama in Ethiopia. 12 health extension workers (HEW) from the sites areas underwent comprehensive training, in part based on experiences from prior citizen science based research into community level CVD risk perception. All health care practitioners at referral clinics had been provided with training in NCD care by either government or NGO based courses. Community participants were identified by door-to-door screening, given introductory education into the study using a non-language-based set of visual tools oriented by CS research, and a standard structured questionnaire with participant information captured on a mobile tablet and later transferred to a database for analysis. Community participants were identified with at least a 10% 1-year CVD risk as assessed by a modified Framingham tool using body mass index in replace of cholesterol, referred to neighboring health clinic, and followed up by HEW one month later. Results: 95% of community members (aged ³40) identified agreed to participate in the study; 9.1% of participants from rural and 13.9% from urban communities had 10-year CVD risk score >10%. 62% had reported hypertension, 22% diabetes, 49% were overweight, 12% were smokers. After one month follow-up, 74% of those with risk had attended a local clinic. Those with prior diagnoses of hypertension and/or diabetes had identical rates of clinic attendance as those without such diagnoses. Of those attending clinics, 63% were provided medication scripts, and 97% provided with counselling. 89% of those attending clinics indicated they intended to continue future follow-up. Among those who did not follow-up, 25% cited financial difficulty, 45% inconvenience, and 25% reported 'there is no point to attend'. Conclusion: We observed high rates of acceptance of screening and referral to health clinics in Ethiopia by a pilot community level Cardiovascular disease screening informed by prior citizen science research into CVD risk perception.